2017
DOI: 10.1007/s11845-017-1571-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery in lower limb arthroplasty in the Irish setting

Abstract: ERP has the potential to significantly reduce overall length of stay after hip and knee arthroplasty and could have a considerable benefit in the Irish setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The key finding was that LoS was significantly associated with patient surgical and management factors. Patient age at surgery and the presence of comorbidities have been extensively reported as factors affecting LoS 4,5,10 and this was supported by the present findings. However, we also found that the time to first mobilization, discharge destination other than home, and the presence of complications also extended LoS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The key finding was that LoS was significantly associated with patient surgical and management factors. Patient age at surgery and the presence of comorbidities have been extensively reported as factors affecting LoS 4,5,10 and this was supported by the present findings. However, we also found that the time to first mobilization, discharge destination other than home, and the presence of complications also extended LoS.…”
Section: Discussionsupporting
confidence: 91%
“…ERP introduction has an excellent track record in reducing average LoS, including within the regional hospital setting. 3,4 In our regional hospital, efforts have been made to reduce LoS over a 5-year period, but as yet have not been documented into a formal protocol. Attempts to reduce LoS further cause concern for some members of the surgical community and other health care workers, due to the perceived elevated risk of hospital readmission after discharge.…”
mentioning
confidence: 99%
“…One important result from our study shows a shorter stay was not significantly associated with increased complications, proved also in a study by Scholes et al [1] . The former sentence is contrasted by Galbraith et al [7] , in his study stated that shorter hospital stays may reduce the quality of care and poorer outcomes if patients are discharged even before they are ready for it. Notably increasing age, female sex, presence of comorbids, presence of a complication, Low preoperative hemoglobulin and albumin, postoperative blood transfusion was associated with increased LOS and proved costly a treatment, burdening the patient.…”
Section: Discussionmentioning
confidence: 94%
“…Notably increasing age, female sex, presence of comorbids, presence of a complication, Low preoperative hemoglobulin and albumin, postoperative blood transfusion was associated with increased LOS and proved costly a treatment, burdening the patient. The patients' age at surgery and presence of comorbids has been extensively reported to increase LOS [1,2,4,5,7,8] younger age with decreased LOS are explained in literature [7] . Older patients are liable to be physically weak, furthermore, they need caregiver support than the younger age group which can increase LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception in the early 2000s, the ERP has been introduced to a variety of different surgical specialties in the UK. It has been particularly popular in patients undergoing surgery for colorectal cancer, and in hip and knee arthroplasty in orthopaedics [ 13 , 14 ]. Although minor adaptations may be made to the ERP depending on the requirements of the pathologies it is set up to encompass, the emphasis remains on the optimization of the patient from the outset of admission.…”
Section: Discussionmentioning
confidence: 99%